2020
DOI: 10.1038/s41467-020-16221-9
|View full text |Cite
|
Sign up to set email alerts
|

Constructing chiral bicyclo[3.2.1]octanes via palladium-catalyzed asymmetric tandem Heck/carbonylation desymmetrization of cyclopentenes

Abstract: Transition-metal-catalyzed tandem Heck/carbonylation reaction has emerged as a powerful tool for the synthesis of structurally diverse carbonyl molecules, as well as natural products and pharmaceuticals. However, the asymmetric version was rarely reported, and remains a challenging topic. Herein, we describe a palladium-catalyzed asymmetric tandem Heck/carbonylation desymmetrization of cyclopentenes. Alcohols, phenols and amines are employed as versatile coupling reagents for the construction of multifunctiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 55 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…This reaction exhibited good functional group tolerance, and it has been implemented as a key step in the syntheses of the natural product coixspirolactam A and of an effective CRTH2 receptor antagonist. Indeed, They pro- In 2020, Lin and Yao et al [52] reported a Pd-catalyzed asymmetric tandem Heck/carbonylation desymmetrization of cyclopentenes that produced bicyclo[3.2.1]-octanes, which are found in several bioactive natural products. Employing Pd 2 (dba) 3 •CHCl 3 (or Pd(dba) 2 ) as the catalyst and (S)-difluorphos as the ligand, various chiral bicyclo[3.2.1] octane products bearing one all-carbon quaternary and two tertiary carbon stereogenic centers were synthesized in 50%-98% yields and 88%-97% ee.…”
Section: Palladium-catalyzed Heck Carbonylationsmentioning
confidence: 99%
“…This reaction exhibited good functional group tolerance, and it has been implemented as a key step in the syntheses of the natural product coixspirolactam A and of an effective CRTH2 receptor antagonist. Indeed, They pro- In 2020, Lin and Yao et al [52] reported a Pd-catalyzed asymmetric tandem Heck/carbonylation desymmetrization of cyclopentenes that produced bicyclo[3.2.1]-octanes, which are found in several bioactive natural products. Employing Pd 2 (dba) 3 •CHCl 3 (or Pd(dba) 2 ) as the catalyst and (S)-difluorphos as the ligand, various chiral bicyclo[3.2.1] octane products bearing one all-carbon quaternary and two tertiary carbon stereogenic centers were synthesized in 50%-98% yields and 88%-97% ee.…”
Section: Palladium-catalyzed Heck Carbonylationsmentioning
confidence: 99%
“…Palladium-catalyzed asymmetric domino Heck reaction is one of the most powerful methods for the construction of quaternary stereocenters. 26,27 Through trapping of the in situ generated alkyl-PdX intermediate, various enantioselective domino reactions, including Heck tandem coupling with azoles, 28,29 (dearomative) Heck-Sonogashira reaction, [30][31][32] Heck-Suzuki reaction, 33,34 and Heck-carbonylative reaction [35][36][37][38] have been developed for the synthesis of valuable structures (Scheme 1A). Alternatively, by switching the cross-coupling of alkyl-PdX to reductive elimination, intriguing reductive Heck and Heck carboiodination reactions have been reported (Scheme 1A).…”
Section: Introductionmentioning
confidence: 99%
“…1 Intramolecular enantioselective carbopalladation of 1,1-disubstituted C−C double bond represents an elegant approach to generating chiral σ-alkylpalladium species, which can be in situ trapped by various nucleophiles such as cyanide, azole, and hydride as reported by the groups of Zhu, 2−7 Lautens, 8 Jia, 9−11 Diaz, 12 Zhou, 13,14 Tong, 15,16 Zhang, 17−20 Lu, 21 and Lin and Yao (Scheme 1a). 22,23 Transition-metal catalyzed C−C σ-bond activation has received considerable attention in the past decade. 24−29 Owing to the inherent high ring strain, C−C σ-bond of cyclobutanones can be easily cleaved, and Rh-and Ni-catalyzed enantioselective C−C bond activation of prochiral cyclobutanones has been established by the groups of Murakami, 30−32 Cramer, 33−35 and Dong.…”
mentioning
confidence: 99%